Nutrition Profile, Body Composition, Somatotype of Adolescent Football Athlete and It’s Correlation with Performance - Kurnia Mara'atus Solichah; Dittasari Putriana (Universitas Negeri Semarang, 2025)
Background: Performance in athletes is influenced by multiple factors, including the athlete's physical profile, technique, and tactics related to the sport being played. Objective : The objective of this research is to analyze the nutrition profile, body composition, and somatotype of adolescent football athletes and determine their correlation with athletes' performance. Methods: This study uses a quantitative descriptive technique with a measurement survey method. The study took place in June-August 2023, with 35 adolescent football athletes involved as respondents. The data obtained are presented in the form of a frequency distribution for each indicator. Statistical analysis with SPSS was conducted for correlation analysis. Results: Based on the results of the study, it is known that 86.11% of athletes have good nutritional status, and 13.89% of athletes have excess nutritional status. The results of measuring the percentage of body fat showed 77.78% in the normal category, 19.44% in the high category, and 2.78% in the low category. The dominant somatotype categories in athletes are endomorph and ectomorph. Statistical analysis shows that performance has significantly correlated with supraspinal skinfold (p=0.020), femur (p=0.027), and ectomorph (p=0.021). Conclusion: It can be concluded that for adolescent football athletes, body linearity and supraspinal fat folds are a significant influence on performance.